The Diversity of Plankton in the Pinang Dalam Lake, Buluh Cina Village, Siak Hulu, Kampar, Riau Province - Galuh Putri Ratna Ningtyas; Efawani '; Yuliati ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
A study on the diversity of plankton in Pinang Dalam Lake was conductedfrom January – March 2014. This research aims to identify the diversity ofplankton in Pinang Dalam Lake. There were three stations with 3 sampling pointsin each station. Samples were taken 3 times, once a week and they were analyzedin the laboratory of Ecology and Aquatic Environment Management of Fisheriesand Marine Science Faculty of Riau University.Result shown that the plankton obtained were consist of 7 classes ofphytoplankton and 7 classes of zooplankton with 43 species as following:Bacillariophyceae Class (7 species), Cyanophyceae (4 species), Chlorophyceae (8species), Dinophyceae (2 species), Chrysophyceae (2 species), Euglenophyceae (4species), Xanthophyceae ( 2 species), Brachionidae (1 species), Maxillopoda (4species), Monogonata (3 species), Tubulinea (1 species), Copepoda (1 species),Ciliata (1 species) and the last is Bdelloidea (3 species). The average ofphytoplankton abundance was around 262222 – 328711 cells/l. Diversity index(H’) was 1.22 - 1.87, dominance index (C) was 0.51 - 0.67, and equitabity index(E) was 0.25 - 0.38. The average of zooplankton abundance was around 4622 –5333 ind/l. The result of this study based on the value of the phytoplankton,Pinang Dalam Lake including the type of lake that has a high abundance ofphytoplankton.Keywords : Phytoplankton Abundance, Pinang Dalam Lake, Oxbow Lake